Visual And Anatomical Outcomes of Pars Plana Vitrectomy in Refractory Diabetic Macular Edema - Khaqan, Hussain Ahmad; Imtiaz, Usman; Bukhsh, Husnain Muhammad; Rehman, Hafiz Ateeq ur; Naz, Raheela; Shabbir, Usman (Pakistan Journal of Ophthalmology, 2020)
Purpose: To find the visual and anatomical outcomes of pars plana vitrectomy in cases of refractory diabetic macular edema. Study Design: Quasi Experimental study. Place and Duration of Study: Department of Ophthalmology, Lahore General Hospital from January 2013 to April 2019. Material and Methods: Seventy-six patients between the age of 18 and 60 years of both genders having refractory diabetic macular edema with macular thickness of 400 micrometers or more on OCT were enrolled. Informed consent was taken. Detailed preoperative workup including visual assessment, examination on slit lamp using 90D or 78D lens for assessment of macular edema and OCT was done. Patients underwent pars plana vitrectomy, ERM, and ILM peeling. Visual assessment and macular thickness was recorded 4 weeks after surgery. Results: This study included 76 patients with the mean age of 48.15 ± 8.16 years. Patients were further categorized according to age into 2 groups. The gender distribution of patients showed that most of the participants were female in this study. Mean duration of Diabetes Mellitus was 9.95 ± 6.29 years. Most of the patients did not have previous history of laser and only three patients (3.9%) did not receive Intravitreal Anti-VEGF. Mean preoperative visual acuity was 0.44 ± 0.13 while postoperative visual acuity was 0.876 ± 0.18 (P = 0.000). Similarly, significant decrease in macular thickness was observed after the procedure (P = 0.000). Conclusion: Pars plana vitrectomy, ERM and ILM peeling can be an effective treatment option for refractory diabetic macular edema.